Analisis Strategi Guru dalam Menanamkan Sikap Kejujuran Melalui Pembelajaran IPS terhadap Siswa Kelas VIII SMPN 2 Kalidawir - Da’i Syahrizal; Bagus Setiawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research was motivated by the findings of dishonest behavior among SMPN 2 Kalidawir students, such as cheating during exams and dishonesty in daily social interactions. This condition shows that the value of honesty has not developed optimally. Therefore, this study aims to analyze social studies teachers' strategies in instilling honesty in grade VIII students and identify supporting and inhibiting factors in the process. The focus of the research includes two things: (1) teachers' strategies in instilling honesty through social studies learning, especially materials related to social interaction and students' daily lives; and (2) factors that affect the success of teachers in shaping the character of students' honesty. The approach used is descriptive qualitative research with data collection through observation, interviews, and documentation. This method allows researchers to gain an in-depth understanding based on the interpretation of phenomena found in the field. The results of the study show that the strategy of instilling honesty values is carried out in an integrated manner through the example of teachers, habituating honest behavior, and providing positive motivation during the learning process. Teachers also integrate the value of honesty into relevant social studies materials and provide real examples in daily life. Supporting factors for the success of this strategy include consistent teacher examples, a conducive school environment, and targeted and collaborative student program support. However, there are inhibiting factors such as the influence of the environment outside the school, academic pressure, and diverse socioeconomic conditions of students. This research makes an important contribution to strengthening character education through social studies learning at the junior high school level.